EKSPERIMEN PESAWAT ATWOOD BERBASIS PENGOLAHAN APLIKASI TRACKER UNTUK MENGAMATI FENOMENA GERAK LURUS BERATURAN DAN GERAK LURUS BERUBAH BERATURAN PADA PEMBELAJARAN FISIKA SMA - Firman Nugraha; Resti Wulansari; Inka Danika; Vina Nurafiah; Asri Nur Lathifah; Fitri Nurul Sholihat; Hana Susanti; Muhamad Gina Nugraha; Kartika Hajar Kirana (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2017)
Physics is one of science branch that become the cornerstone of many of advanced technology development, so the process of learning physics should not only focused on the concept mastery but also concerning the discovery aspect. In that case, experiment activity has been really important in learning physics. One of the most common experiment activity which used to explain uniform rectinilier motion and accelerated uniform rectinlier motion is using Atwood Machine. From the observations, it is showed that the measure of the motion parameter has done manually using stopwatch and ruler. The result from this experiment was subjective and also it was cannot give exact characteristic of this two motion. One of the solution for this problem is use tracker application. In this experiment, a body is recorded using High Definition camera with 24 frame per second shutter speed. The result from data processing with tracker has shown that the graphic of position depend on time for uniform rectilinier motion (y=f(t)) is a linier line with positive gradient and the graphic of the velocity depend on time (v=f(t)) is flat line shaped. For the uniform accelerated rectilinier motion, the graphic of position depend on time (y=f(t)) is a graphic from quadratic function and the graphic of the velocity depend on time (v=f(t)) is a linier line with positive gradient. Based on the result of the data analysis, it is concluded that the use of tracker application on atwood machine is able to show the characteristic of uniform rectilinier motion and uniform accelerated rectilinier motion so it is worth to use in physics learning at school. Keywords: Uniform Accelerated Rectilinier Motion, Uniform Rectilinier Motion, Tracker, Atwood Machine.